FORMATION OF THE SOFT SKILLS FOR STUDENTS OF ENERGY SPECIALTIES THROUGH THE IMPLEMENTATION OF ACTIVE LEARNING METHODS INTO THE EDUCATIONAL PROCESS - ДЕРЕВ’ЯНКО, Д. Г.; ШОВКАЛЮК, М. М. (Technologies and Engineering, 2024)
Ukraine's international obligations in the field of energy and environmental security, the need to implement state programs on the energy efficiency increase and municipal energy development plans requires a large number of qualified specialists with relevant professional competencies. Purpose of the study. Improvement of the quality of education of students of energy specialties by using the experience of implementation of active learning methods which develop both professional skills for solving specialized tasks of calculating technical and economic indicators of energy-efficient projects ("hard skills"), and extra-professional competencies ("soft skills") into the educational process of energy management students. Methodology. The study included an analysis of the effectiveness of the implementation of active learning methods and educational role-playing games for the development of professional competencies of students of energy specialties. The creation of professional-oriented educational situations contributes to the formation of communicative and personal competencies of future specialists in the field of energy management and energy audit. The results. Active learning methods have been implemented into the educational process for students of energy specialties, namely: business games, debates, public speeches with the defense of adopted technical decisions, field trips to enterprises with conducting research and scientific-practical seminars. The experience of organizing and conducting a summer school of English language communication for the development of communication competence of master students was obtained. Training of dual education students on the basis of energy-generating and energy-supplying enterprises is organized. Educational role-playing business games have been implemented for energy management students as part of the study of elective disciplines. Scientific novelty. Based on the analysis of active learning methods, the procedure and recommendations for implementation of three business games for energy management students as part of the study of individual educational components, have been formulated. The implementation of which will contribute to higher quality training of students of energy specialties. Practical value. Business games and other methods of active learning were developed, adapted and implemented in the educational process of students of the "Energy Management and Energy-Efficient Technologies" educational programs at the Igor Sikorsky Kyiv Polytechnic Institute. The implemented active learning methods within the framework of two professional educational programs for students of energy specialties of the first (bachelor) and second (master) levels of higher education have positively proven themselves by forming students' extra-professional competencies ("soft skills").